Marketing Communication Strategies of Cafe Tutur Rasa in Supporting the Existence of Individuals with Hearing Impairments - Mutiara Mujahidah Hanifah; Didik Hariyanto (COMMICAST, 2025)
Cafe Tutur Rasa is part of a social program by Midtown Hotels Indonesia, established as a form of support for people with disabilities, particularly those who are deaf. This study aims to analyze the marketing communication strategies implemented by Cafe Tutur Rasa in supporting brand existence and promoting social inclusion for individuals with hearing impairments. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that Cafe Tutur Rasa applies a marketing communication strategy based on the Mega Marketing Mix theory, which includes several key elements. In terms of Product, the cafe offers coffee with an original taste and unique menu variations in each cafe unit. Regarding Price, the cafe maintains affordable pricing despite being located in the center of Surabaya. For Place, the cafe is situated in a strategic and easily accessible area. The Promotion aspect is carried out through collaborations with influencers, digital media campaigns, and special programs for hotel guests. The Power element is reflected in the involvement of deaf baristas as part of the cafe’s social mission, strengthened by the institutional support of the hotel to ensure credibility and operational sustainability. Public Relations activities are implemented through events that involve deaf baristas and the general public to increase publicity and raise awareness of the cafe’s social initiatives. The results demonstrate that the Mega Marketing Mix strategy is effectively utilized to strengthen brand positioning while enhancing public awareness of inclusivity issues. Theoretically, this study contributes to expanding the application of the Mega Marketing Mix concept within the context of disability-based inclusive business practices. Practically, the findings offer a strategic communication model that can be adopted by other inclusive cafes in Indonesia.